Assessment of laparoscopic skills: comparing the reliability of global rating and entrustability tools - Kameela Alibhai; Amanda Fowler; Nada Gawad; Timothy J Wood; Isabelle Raîche (Canadian Medical Education Journal, 2022)
Background: Competence by design (CBD) residency programs increasingly depend on tools that provide reliable assessments, require minimal rater training, and measure progression through the CBD milestones. To assess intraoperative skills, global rating scales and entrustability ratings are commonly used but may require extensive training.  The Competency Continuum (CC) is a CBD framework that may be used as an assessment tool to assess laparoscopic skills. The study aimed to compare the CC to two other assessment tools: the Global Operative Assessment of Laparoscopic Skills (GOALS) and the Zwisch scale.